The new philosophy of science: limitations of the internalist notion of scientific activity (Research, Society and Development, 2022)
This article, in fact, forms part of a more extensive investigation into different schools, currents or epistemological movements and their respective contributions, in this aspect, to the formation of teachers in Natural Sciences. In this sense, the movement called New Philosophy of Science is included here and, in particular, the efforts of its most prominent member, Thomas Kuhn. Therefore, the narrative bibliographic review is chosen as a method, based on primary and secondary sources, in addition to the support of introductory manuals of Philosophy of Science. The objective of this is to clarify some particularities of the referred movement and to reflect on it, as well as to encourage the practice of epistemologically grounded debates with a view to a deepening that, of course, will help in an integral formation of the participants. The results point to the extreme need for an “updating” of discourses and debates in an appropriate space, that is, in the training of teachers in that area. In terms of conclusion, it becomes evident the need to establish in the curricula of these courses, a clear and notorious concern with an effective approach to the different epistemological conceptions so that we can contribute, in effect, to a holistic training of future teachers, equipped with this very important tool called epistemology.